The use of fractal geometry in determination of fracture toughness of metakaolinite modified concrete - Konkol, Janusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The aim of the paper is to present the results of experiments on concretes after 180 days of hardening with metakaolinite addition. Measurements of compressive strength fc, critical stress intensity factor KIcS and fractal dimension Dm were performed. The plan included nine measurement points. Water/binder ratios ranging from 0.35 to 0.54, and the metakaolinite additives in the amount ranging from 2.1 to 14.9 % relative to the mass of binder were used as independent variables. Statistically significant correlations were given. The proposed solutions can be used in designing the concrete with metakaolinite, which enables the prediction of KIcS after 180 days of hardening concrete with no need for destructive tests.